A Novel Electrode With Electromagnetic Tip Tracking in Ultrasonography-Guided Radiofrequency Ablation: A Phantom, Ex Vivo, and In Vivo Experimental Study. Issue 2 (February 2015) - Kang, Tae Wook; Lee, Min Woo; Choi, Seung Hee; Rhim, Hyunchul; Lim, Sanghyeok; Song, Kyoung Doo; Min, Ji Hye; Choi, Seo-youn; Lim, Hyo Keun; Yang, Jehoon
Abstract : Objectives: The objective of this study was to compare the targeting and ablation performance between a newly developed radiofrequency (RF) electrode embedded with an electromagnetic position sensor (EMPS) at the electrode tip and a conventional RF electrode. Materials and Methods: The institutional animal care and use committee approved this study. The targeting of paint balls within phantoms was performed under ultrasonography guidance by 2 radiologists (beginner vs expert) with an "in-plane" and "out-of-plane" approaches using the new RF electrode and a conventional RF electrode (n = 20 for each method). To evaluate the targeting performance, the electrode placement time and the number of electrode pullbacks for redirection were compared between the 2 electrodes. The ablation performance was also compared by analyzing the ablation volumes in ex vivo bovine and in vivo porcine livers (n = 30 and n = 24, respectively) and the cellular viability of the ablation zone in in vivo specimens. Results: In the phantom study, the RF electrode embedded with an EMPS showed a significantly shorter electrode placement time compared with the conventional RF electrode in both the in-plane and out-of-plane approaches by both radiologists ( P < 0.05). The electrode pullback rate for both radiologists was lower in the new RF electrode than in the conventional RF electrode, but it did not reach statistical significance in the in-plane approach by the expert ( P = 0.059). The ablation volumes analyzed with and without cellular viability in the ex vivo and in vivo studies were not significantly different between the 2 electrodes ( P > 0.05). Conclusions: The RF electrode embedded with an EMPS is faster than the conventional electrode in the electrode placement into the target lesions. The ablation performance is not significantly different between the 2 electrodes.